Antibacterial and Antioxidant Activity of Protein Hydrolysate Extracted from different Indonesian Avian Egg White - A. S. Sukarno; Nurliyani Nurliyani; Yuny Erwanto; Satyaguna Rakhmatulloh; Rifqi Rifqi (Jurnal Sain Peternakan Indonesia, 2023)
White egg contains the most significant protein source that has been explored to give more benefit for health purposes.  This study evaluated the potential of antibacterial and antioxidant activity of white egg protein hydrolysate extracted from Indonesian avian eggs.  The avian egg materials used local Indonesian chicken eggs (kampung chicken), chicken breed eggs, duck eggs, and muscovy duck eggs.  The white egg was extracted by organic solvent and produced protein extracted which was dominated by ovalbumin and ovotransferrin.  The protein extracted was hydrolyzed by pepsin and then powdered using a freeze dryer.  Antibacterial and antioxidant activity was evaluated by agar well diffusion technique and 2,2-Diphenyl-1-picryl hydroxyl (DPPH) radical scavenging method.  All samples showed antimicrobial activity against Salmonella sp., Escherichia coli, Staphylococcus aureus, Bacillus cereus, and Bacillus subtilis with a concentration of protein hydrolysate at 40 mg/mL.  The antioxidant activity between avian species was different and dose-dependent.  Protein hydrolysate extracted from duck white egg exhibited the highest radical scavenging activity (65%) at 10 mg/mL concentration.  However, all white egg protein hydrolysate extracted from Indonesian avian eggs can potentially help reduce oxidation and microbial deterioration.